Agrobiodiversity, school gardens and healthy diets: Promoting biodiversity, food and sustainable nutrition - Hunter, Danny; Monville-Oro, Emilita; Burgos, Bessie; Rogel, Carmen Nyhria; Calub, Blesilda; Gonsalves, Julian Francis; Lauridsen, Nina Olsen (Routledge, 2020)
This book critically assesses the role of agrobiodiversity in school gardens and its contribution to diversifying diets, promoting healthy eating habits and improving nutrition among schoolchildren as well as other benefits relating to climate change adaptation, ecoliteracy and greening school spaces. It features international case studies, spanning both developed and developing nations.